Game AI Pro 360. Guide to architecture - Rabin, Steve (Boca Raton : CRC Press, 2020)
"Cutting-edge game AI architecture primarily from game developers of shipped commercial games. The book acts as a toolbox of techniques that can be applied to many common and not-so-common situations"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer games -- Programming; Computer games -- Design; Video games; Software architecture; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design